Educational psychology perspective on constructive, social play and academic performance of primary school children in Nigeria - Suleiman, Abdullahi; Abdulkareem, Habibat Bolanle (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
Poor performance in numeracy at the primary level of education may result from inadequate instructional materials, methods, techniques, or strategies used in teaching it. This study investigated the effects of constructive and social play on pupils' academic performance in numeracy in Niger State. The study examined the interaction effects of constructive, social play, gender, and school type on pupils' academic performance in numeracy in Niger State. The study adopted the social-cultural theory of Lev Vygotsky. The research design used was a pretest-posttest control group non-equivalent quasi-experimental design. A stratified random sampling technique was adopted to select six schools for the study. The instrument used was Numeracy Performance Test (NPT). The Pearson Moment Correlation Coefficient was used to ascertain the reliability coefficient of 0.76 coefficients that were obtained. Frequency counts, percentage, mean, and ANCOVA were used to analyze the data collected. The results revealed that social and constructive play substantially impacted pupils' numeracy performance in Niger State. There was no gender-related difference in student performance in maths and no statistically significant interaction between therapy and gender on pupils' performance in numeracy. In Niger State, there was no discernible correlation between the type of school and pupils' performance in numeracy. Gender and school type did not significantly affect pupils' academic performance in numeracy, suggesting that social play and constructive play increased higher performance in math than the traditional style of instruction.